2006
DOI: 10.1097/01.smj.0000209093.78617.3a
|View full text |Cite
|
Sign up to set email alerts
|

The Multidisciplinary Evaluation and Management of Cleft Lip and Palate

Abstract: Cleft lip with or without a cleft palate (CLP) and cleft palate alone (CPA) are common birth defects, with a combined birth prevalence of about 1 to 2/1,000. Affected children have a number of medical issues and potential complications, and therefore require a wide variety of healthcare specialists beyond plastic surgeons and dental specialists. For this reason, the best environment in which to deliver this care is a multidisciplinary cleft clinic (MCC) that features a team of healthcare providers, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 16 publications
0
78
0
8
Order By: Relevance
“…Worldwide, of all the orofacial clefts, 20% of clefts were reported as isolated cleft lip (18% unilateral and 2% bilateral), 50% were CLP (38% unilateral and 12% bilateral), and 30% were CP. 5 The The United States is highly multiethnic, and reports have indicated that CLP is highest in whites, intermediate in Hispanics, and lowest in blacks. 20 The results of our study closely recapitulated earlier reports, with a 51.3% incidence of orofacial cleft in whites, 26.4% in Hispanics, and 4.9% in blacks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Worldwide, of all the orofacial clefts, 20% of clefts were reported as isolated cleft lip (18% unilateral and 2% bilateral), 50% were CLP (38% unilateral and 12% bilateral), and 30% were CP. 5 The The United States is highly multiethnic, and reports have indicated that CLP is highest in whites, intermediate in Hispanics, and lowest in blacks. 20 The results of our study closely recapitulated earlier reports, with a 51.3% incidence of orofacial cleft in whites, 26.4% in Hispanics, and 4.9% in blacks.…”
Section: Discussionmentioning
confidence: 98%
“…4 Children who are born with cleft lip and palate present with a number of medical issues and potential complications, requiring a multidisciplinary cleft team for their management. 5 Epidemiologic studies have delineated differences in the incidence of cleft lip and palate based on ethnicity, age, gender, and geographic regions. Often, these studies have used data from state registries such as Texas, Florida, and California or some international databases.…”
mentioning
confidence: 99%
“…For both CL 6 P and spina bifida, the medical care typically required during the first few months of life is complex, and it is recommended that these conditions be treated by specialized teams of providers. [23][24][25] All of the family-level risk factors exhibited were associated with substantiated maltreatment (relative risk $1.5). Poverty-related factors, such as low maternal education, Medicaid use, and multiple previous births, were associated with 2-to 3-fold increases in risk for maltreatment in this study and have been consistently associated with maltreatment in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cleft palate is a relatively common congenital malformation with an incidence of between one and two in 1000 live births (1). The severity is variable and ranges from occult to overt; the causes are numerous and range from syndromic/ genetic to teratogenic/environmental to isolated/idiopathic; the management is often complex and ranges from straightforward surgical closure to multidisciplinary surgical and cleft team care.…”
Section: Cleft Palatementioning
confidence: 99%